Mathematical Modeling of DNA Damages in Irradiated Cells at Different Oxygenation Degrees - Bondarenko, M.A.; Knigavko, V.G.; Zaytseva, O.V.; Rukin, A.S. (Кибернетика и вычислительная техника, 2019)
The purpose of the paper is to develop a mathematical model of DNA damage in irradiated cells at different degrees of their oxygenation; to study the dependence of the number of radiation damages of DNA per unit volume of the irradiated medium on the radiation dose and the concentration of oxygen in the medium; to estimate the cell cycle duration depending on the oxygen concentration. Results. A mathematical model of oxygen effect in cells in the case of irradiation by X-rays or gamma-radiation is proposed. On the basis of this model, the dependence of the number of radiation DNA damages in the unit volume of the irradiated medium on the radiation dose and the concentration of oxygen in the medium is obtained. Triple damage to DNA molecules is determined by primary radiation damage and attacks of two radicals of oxygen on the DNA molecule. Метою статті є розроблення математичної моделі пошкодження ДНК в опромінених клітинах за різного ступеня їх оксигенації; вивчення залежності кількості радіаційних пошкоджень ДНК на одиницю об'єму опроміненого середовища від дози випромінювання та концентрації кисню в середовищі; оцінювання тривалості клітинного циклу залежно від концентрації кисню. Результати. Запропоновано математичну модель кисневого ефекту в клітинах у разі їх опромінення рентгенівським або гамма випромінюванням. На основі цієї моделі отримано залежність кількості радіаційних пошкоджень ДНК в одиничному об'ємі опроміненого середовища від дози опромінення та концентрації кисню в середовищі. Трикратне пошкодження ДНК визначається первинним радіаційним пошкодженням та атакою двох радикалів молекули кисню на молекулу ДНК. Предложена математическая модель кислородного эффекта в клетках при облучении их рентгеновским или гамма-излучением. На основе этой модели получена зависимость числа радиационных повреждений ДНК в единице объема облученной среды от дозы излучения и концентрации кислорода в среде. Объяснен факт, что максимальное значение коэффициента кислородного усиления для фотонных излучений не может быть больше 3. Изучено влияние потенциально летальных повреждений на выживаемость клеток в условиях облучения. Оптимальным показателем выраженности эффекта потенциально летальных повреждений является продолжительность клеточного цикла. Построена математическая модель, которая позволяет оценить величину этого показателя в зависимости от концентрации кислорода.